Faktor Determinan Opini Audit Going Concern - Rafrini Amyulianthy (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
This research purpose to determine the effect of financial condition of company, the size of audited company, the company's growth and reputation of the Public Accounting Firm to going-concern audit opinion on the company's listed on Indonesia Stock Exchange. Companies sample in this research are industrial trade, services and investment covered years 2007-2012 which 20 companies with. Hypothesis tested by using logistic regression models. The test results showed that the financial conditions using by bankruptcy prediction model Altman Z - Score Revised had positive effect but not significant to going-concern audit opinion. The size of the company which is using by log total assets had negative effect and significant to goingconcern audit opinion. Meanwhile the company's growth had positive effect but not significant to going-concern audit opinion. The public accounting firm's reputation using by the scale of the auditor (affiliated with the Big Four KAP), positive effect but not significant to goingconcern audit opinion.